IMMUNOGISTOCHEMICAL CHARACTERISTICS OF MESENTERIAL LYMPH NODES IN OFFSPRING OF RATS BORN UNDER CHRONIC EXPOSURE TO PESTICIDES (World Bulletin of Public Health, 2024)
The purpose of the work is to study the features of postnatal development of mesenteric lymph nodes in the offspring of female rats chronically intoxicated with pesticides. The studies were conducted on 60 sexual, non-pregnant, nonbreeding white female rats weighing 160-180 g and 473 (control group - 285, experimental group - 188) rat pups born from them. Postnatal morphogenesis of mesenteric lymph nodes was studied using morphological and morphometric research methods. The results obtained showed a significant disruption of the postnatal processes of development of mesenteric lymph nodes in offspring born with chronic exposure to pesticides.
Keywords: fipronil; offspring; postnatal ontogenesis; mesenteric lymph nodes.